Azathioprine dose reduction in inflammatory bowel disease patients on combination therapy: an open‐label, prospective and randomised clinical trial. Issue 2 (27th April 2017) - Roblin, X.; Boschetti, G.; Williet, N.; Nancey, S.; Marotte, H.; Berger, A.; Phelip, J. M.; Peyrin‐Biroulet, L.; Colombel, J. F.; Del Tedesco, E.; Paul, S.; Flourie, B.
Summary: Background: Infliximab (IFX) combined with azathioprine (AZA) is more effective than IFX monotherapy in inflammatory bowel disease (IBD). Aim: To identify the AZA optimal dose that is required for efficacy when receiving combination therapy. Methods: Patients with IBD in durable remission on combination therapy were enrolled in a 1‐year, open‐label, prospective trial after randomisation into three groups: AZA steady (2‐2.5 mg/kg/day, n=28) vs AZA down (dose was halved 1‐1.25 mg/kg/day, n=27) vs AZA stopped (n=26). Primary endpoint was failure defined as occurrence of a clinical relapse and/or any change in IBD therapy. Results: Eighty‐one patients were included. Five (17.9%), 3 (11.1%), and 8 (30.8%) patients experienced failure at 1 year in groups AZA steady, AZA down and AZA stopped, respectively ( P =.1 across the groups). The median trough levels of IFX at inclusion were close to those measured at the end of follow‐up in group AZA steady (3.65 vs 3.45 μg/mL, P =.9) and in group AZA down (3.95 vs 3.60 μg/mL, P =.5), whereas these levels dropped from 4.25 to 2.15 μg/mL ( P =.02) in group AZA stopped. Four (14.3%), four (14.8%) and 11 (42.3%) patients experienced an unfavourable evolution of IFX pharmacokinetics in groups AZA steady, AZA down and AZA stopped, respectively. A threshold of 6‐TGN <105 pmoles/8.10 8 RBC was associated with an unfavourable evolution of IFX pharmacokinetics. Conclusions: Under combination therapy, AZA dose reduction, but not withdrawal, appears to be as effective as continuation of AZA at full dose. Abstract : Linked Content This article is linked to Meijer and de Boer, and Roblin et al papers. To view these articles visithttps://doi.org/10.1111/apt.14375 andhttps://doi.org/10.1111/apt.14385 .